Bing Chat AI for Learning Supplement - I Made Pustikayasa; Ni Wayan Purnawati; I Nyoman Alit Arsana (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2023)
The development of a student is very dependent on the learning environment, such as the learning environment at school, at home, and in the surrounding community. Currently, the way students learn is also influenced by the presence of information and communication technology, which is becoming increasingly sophisticated. Artificial Intelligence (AI) is one of the technologies that can be used to obtain summarized information on demand. This AI technology has been integrated into Microsoft Bing. Bing via Chatbot AI is provided on the Microsoft Edge search engine, which has the ability to answer the commands that its users need. This convenience is interesting to discuss in the world of education, especially for students. The presence of Bing Chat AI can be utilized to facilitate students to gain their knowledge as a supplement to the lessons at school.